Entre Britos e Gaudêncios: cultura política e poder familiar nos cariris velhos da Paraíba (1930-1960) - Moreira, Márcio Macêdo (2012)
This study intends to approach the constitution of symbolic Power and of current politic of families Brito and Gaudêncio in Cariris Velhos between 1930 and 1960. Considering that the events happened that to beginning of movement of 1930 caused breaking in the administration plan of Brazilian estates, but also expressed of oligarchy politic permanent. The case of Brito and Gaudencio´s families is an example of adaptation of oligarchy after 1930. The divergence between two families favored to formation of identity of São João do Cariri and the Serra Branca. So, beginning to analyze of politic culture oligarchy in home family, understanding the building of history culture of two town. Understanding he history culture was building by area societies local, that apprehend area of concentration of regional history. This way like theory fundament using the idea of politic culture and symbolic power like mechanician to understand as way of power used by two families. The fountain used approach to research in newspaper, reports spoken, officer documents and works of history paraibana.